Інвентаризація земель: економічні та облікові питання - Голуб, Наталя Олександрівна; Holub, Nataliia (My University, 2025)
UA: У статті розглянуто основні елементи інвентаризації земель сільськогосподарського призначення та її значення для реалізацію земельної політики на місцевому та державному рівні. Інвентаризація земель розглядається з двох точок зору. З одного боку під інвентаризацією розуміють метод державного контролю. З іншого боку інвентаризація є елементом методу бухгалтерського обліку підприємства, за допомогою якого здійснюється контроль та перевірка наявності та стану майна підприємства для забезпечення достовірності даних обліку та фінансової звітності. Визначено основні завдання та мета проведення інвентаризації. Доведено переваги проведення інвентаризації для громад та держави. Сформовано основні проблеми при проведені інвентаризації земель, щодо відсутності документації та неможливості якісного та повного проведення. /// EN: The article examines the main elements of the inventory of agricultural lands and its significance for the implementation of land policy at the local and state levels. Land inventory is considered from two points of view. On the one hand, inventory is understood as a method of state control. On the other hand, inventory is an element of the enterprise's accounting method, which is used to control and verify the availability and condition of the enterprise's property to ensure the reliability of accounting data and financial reporting. The main tasks and purpose of the inventory are determined. The main goal is to create a single database of land resources to ensure effective management, rational use and protection of land. It is determined that land inventory is carried out in order to establish the location of land management objects, their boundaries, sizes, legal status, identify unused, irrationally used or not for their intended purpose, identify and preserve degraded agricultural lands and contaminated lands, establish quantitative and qualitative characteristics of lands necessary for maintaining the State Land Cadastre, identify and correct errors in the information of the State Land Cadastre, exercise state control over the use and protection of lands and make appropriate decisions on their basis by executive authorities and local self-government bodies. The advantages of conducting an inventory for communities and the state are proven. It is established that the inventory of agricultural lands is a key tool for ensuring rational use, legal registration and effective accounting of land resources. At the same time, in practice, this procedure faces a number of significant accounting problems that complicate the implementation of land policy at the local and state levels. These problems hinder the effective use of agricultural land, reduce budget revenues and create obstacles to investment in agriculture. To address these issues, it is necessary to further improve the legislative framework, introduce modern technologies and improve the skills of specialists in the field of land management. It has been proven that strict compliance with regulatory legal acts, a modern approach to work and systematic data updating ensure the rational use of land resources and sustainable development of territories.
Land inventory: economic and accounting issues
Keywords: інвентаризація; земельні ділянки; сільськогосподарські землі; документація; оцінка; управління; контроль; реєстр; inventory; land plots; agricultural land; documentation; evaluation; management; control; registry